Pengaruh Sertifikasi Terhadap Eksistensi Kegiatan Belajar Mengajar Di Sekolah Dasar Kabupaten Lamongan - Wardatul Karomah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Teacher certification is a program from the government, teacher certification is an effort from the government in improving teacher quality coupled with an increase in teacher welfare so that it is expected to improve teacher performance which will have an impact on improving the quality of education in Indonesia on an ongoing basis. Teacher certification is more specific for teacher welfare, improving processes and the quality of education outcomes, and increasing teacher professionalism. Therefore, it is important for the author to reveal the correlation between teacher certification and the existence, professionalism of teachers and improving the quality of education. From the findings of the author, First; There is no significant influence (relationship) between certification of teacher's existence. This is indicated by the results of the analysis of 06.00%, which means that the magnitude of the effect of variable teacher certification benefits on the existence of teachers is classified as very weak. Because teacher certification benefits are not the only variable that affects the existence of a teacher. There are other variables that also influence the existence of a teacher, including the personality and social aspects of a teacher. Second; There is a significant (relationship) influence between teacher certification on teacher professionalism. This is indicated by the analysis results of 31.90%. which means that the magnitude of the influence of teacher certification allowances on teacher professionalism variables is classified as strong enough to influence and predict teacher professionalism variables. Third; There is no significant influence between teacher certification on the quality of education. This is indicated by the results of the analysis of 00,000% or no influence at all. Which means that the magnitude of the effect of teacher certification benefits on the quality of education is very weak because, the quality of education is influenced by many other factors embodied in the 8 (eight) coverage of education quality standards, namely: graduation competency standards, content standards, process standards, education standards and education staff, management standards, educational funding standards, and educational assessment standards.